Sex differences in ground reaction force profiles of ballet dancers during single- and double-leg landing tasks. - Arnwine, R. A.; Powell, D. W (Journal of Dance Medicine & Science, 2020)
It is well known that sex differences exist in landing biomechanics in athletes, and these differences are purported to underlie a prevalence of traumatic knee injuries in females compared to males. However, it remains unknown if these differences also apply to artistic athletes such as dancers. The purpose of this study was to investigate sex differences in ground reaction forces (GRFs) between male and female dancers during single- and double-leg dance-specific landing movements. Fourteen preprofessional and professional ballet dancers (seven female and seven male) performed grand jeté (single-leg landing) and sauté (double-leg landing) jumps onto two force platforms. Visua3D was used to calculate the resulting GRF time-series, and MAT-LAB to select discrete variables of interest including peak vertical GRF, loading rate, landing duration, and vertical impulse. Paired t-tests were used to compare mean GRF variables between male and female dancers. During single-leg landing male dancers had smaller peak vertical GRFs (p < 0.01), greater time-to-peak GRF (p = 0.03), and smaller loading rates (p < 0.01) than female dancers. No differences were observed in vertical impulse during single-leg landing or in any variables during double-leg landing. These results indicate that sex differences in landing GRFs are most evident in single-leg landing and may underlie divergent injury rates in male and female dancers. Further investigation of relevant lower extremity biomechanics during single- and double-leg landing in male and female dancers should be conducted to identify the mechanisms underlying these distinct GRF profiles.